Nutritional properties, bioactive compounds, antioxidant activities, and consumer acceptance of butter cake enhanced with Sangyod rice (Oryza sativa L.) flour - Punfujinda, Chaiyasit; Pongprajak, Apidech; Anunvrapong, Amornrat; Boukaew, Sawai; Chumkaew, Krittin (International Journal of Innovative Research and Scientific Studies, 2025)
Butter cake is a popular bakery product, and developing a formula with enhanced nutritional value would provide a beneficial alternative for health-conscious consumers. Sangyod rice, a local pigmented rice variety from Phatthalung Province, Thailand, offers potential nutritional benefits through its high antioxidant content and economic value for local farmers. This study aimed to develop butter cake using Sangyod rice flour as a wheat flour substitute and evaluate its properties and consumer acceptance. Using an experimental design, butter cakes were prepared with Sangyod rice flour substitutions (40%, 50%, and 60% w/w) and analyzed for their nutritional properties, physical properties, bioactive compounds, antioxidant activities, and consumer acceptance through sensory evaluation (n=100). Results showed that the 50% substitution maintained sensory qualities comparable to the control while improving nutritional profiles. Higher levels of Sangyod rice flour substitution increased fiber content, total phenolic content, total flavonoid content, and antioxidant activities as measured by DPPH and ABTS assays. Consumer surveys demonstrated strong support for local farmers, with 87% product acceptance. These findings suggest that Sangyod rice flour has the potential for developing healthier bakery products while also supporting local agriculture, offering practical implications for commercial product development, and contributing to sustainable income generation for farmers in Phatthalung Province.